ANALISIS PELAKSANAAN PEMUNGUTAN RETRIBUSI KEBERSIHAN (STUDI DI KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA)KOTA PEKANBARU - Dian Putriani; Parjiyana Parjiyana (UIR Press, 2018)
In terms of implementation, the levy charged cleanliness, then the implementation needs to be evaluated to measure the performance of the running. In connection with the issue, then formulated the problem this research is how the implementation of the levy charged for cleanliness in the village of Simpang Tiga subdistrict Bukit Raya Pekanbaru? With the aim of this study to determine the results of voting conducted levy charged hygiene officer (RW), (RT) and to determine the sanction given to the people who shall levy hygiene violate local regulation No.10 of 2012. In this study the data and information collected using a questionnaire. This research can be categorized as a descriptive research with quantitative methods. The research site is in the village of Simpang Tiga subdistrict Bukit Raya Pekanbaru city, with a population of this research is the Head of Bukit Raya, Head. Kep, Works and Supplies, Treasurer Reception, Head Simpang Tiga, Head of Development, Officer Levy Cleanliness collector (RW), the Neighborhood (RT) by using purposive sampling technique and levy payers using simple random sampling technique. Types of data collected included primary data and secondary data. For primary data derived from responses through interviews, questionnaires, observation and documentation. For secondary data through a department that deals with Local Regulation No.10 of 2012. In the analysis of the data, after the data is collected the next step will be clarified and explained by the type and form of data then descriptively. As for the results of the study authors to the conclusion that the implementation of the levy charged for cleanliness in the village of Simpang Tiga subdistrict Bukit Raya Pekanbaru well served seen from the implementation of the levy charged for cleanliness by the clerk to the community has been well served by good although there are still some obstacles, such as sufficient number of people who do not want pay the levy hygiene and of the government itself is still less responsive in taking action against this is because the government is less strict in giving a legal basis to the relevant agencies, and according to the author is expected from the government to carry out this regulation as well as possible for the future in order to realize development and prosperity through a levy hygiene.